Multi-scale study of anti-freeze properties, anti-freeze mechanism and rheological properties of biological antifreeze protein (AFP) modified emulsified asphalt coating. (25th October 2021) - Meng, Yongjun; Lei, Jiechao; Zhao, Qixiong; Hu, Yirong; Yang, Xiaolong; Qin, Pengfei; Qin, Yue
Graphical abstract: Highlights: MD simulation revealed anti-freezing mechanism of AFP-modified emulsified asphalt. Microscopic properties of AFP-modified emulsified asphalt were observed. Rheology and frost resistance of AFP-modified emulsified asphalt studied. MD simulations were consistent with microscopic and freeze resistance test results. Abstract: In this study, biological modification technology was utilized to improve the frost resistance of pavement. By adding biological antifreeze protein to asphalt-based materials, a biomodified emulsified asphalt layer with active antifreeze qualities was created. The mixing mode and its anti-freezing efficacy were investigated using molecular dynamics (MD) simulations. The anti-freezing protein (AFP) was embedded on the asphalt surface, and the structure was completed with asphalt application in two phases. After AFP was attached to the surface of the asphalt binder, the structure remained stable at low temperatures, inhibiting icing and producing a thermal hysteresis differential. Hydrogen bonding and Van der Waals forces influence ice molecule aggregation, and AFP can reduce their effect and induce ice crystal melting. Scanning electron microscopy (SEM) and fluorescence microscopy (FM) revealed that the AFP surface was uneven and anchored to the asphalt surface. The overall structure was complete, with a two-phase distribution that corresponded with the MD results. The anti-icing test results demonstrated that the AFP-modified emulsified asphalt coating effectively inhibited ice condensation and could change the ice crystal growth pattern. The rheological test results revealed that AFP had a slightly negative effect on the high-temperature deformation resistance of the asphalt binder. Environment friendly AFP-modified emulsified asphalt can significantly improve the anti-freezing characteristics of the pavement.